Co-aerosolized Pulmonary Surfactant and Ambroxol for COVID-19 ARDS Intervention: What Are We Waiting for? - Kumar, Pradeep (Frontiers in Bioengineering and Biotechnology, 2020)
After more than 225 days of the first reports of the novel coronavirus from China, COVID-19 pandemic is still on surge. The search for an effective and efficient therapeutic and pharmaceutical intervention is as important and urgent now as it was on Day 1. Majority of the efforts in this direction are towards finding small molecule interventions via repurposing or redirecting the therapeutic approaches. This hypothesis proposes a physical intervention approach directed towards rescuing the complex lung pathology observed in COVID-19 related acute respiratory distress syndrome (CARDS). The loss of content as well as the synthesis and turnover of the surfactant in ARDS has been termed as a “collateral damage”. A synergistic, early stage, cost-effective, pharmaceutically viable, safe, and immediately available solution is hence required. The effectiveness of exogenous surfactant treatment in ARDS has been marred with several limitations as pointed out in various clinical trials and require revised protocols related to surfactant dose and mode of delivery. This hypothesis proposes aerosolized surfactant delivery taking the optimal dosing and coating costs into account along with co-delivery of ambroxol to provide synergistic benefits. Ambroxol is reported to have anti-inflammatory, -oxidant, -viral, and -bacterial activities and has a direct impact on the production and secretion of the surfactant from the alveolar Type 2 cells. If aerosolized, atomized, or nebulized in the form of ambroxol-loaded phospholipid nanovesicles at the early stages of ARDS, depleted surfactant levels may be reinstated and surfactant turnover can be initiated and maintained. The ability to deliver both the components in aerosolized-nebulized form may have a huge impact on alleviating the healthcare burden in low resource settings where the availability of ventilators is limited. In conclusion, the surfactant-ambroxol co-aerosolized intervention approach hypothesized here has implications reaching to clinical and pharmaceutical translation worldwide.